Can Dentists Use Social Media Marketing Effectively While Adhering To Ethical Guidelines? - Analisa, Sylvia; Setyonugroho, Winny (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Instagram is a photo and video-based social media platform that dentists can use to present their brands to potential patients through digital marketing. Before uploading content to social media, dentists must consider several factors, such as visual marketing communication as well as legal and ethical considerations. The purpose of the study is to use the AISAS marketing communication model, advertising ethics, and dentist professional ethics to analyze the content of dental health service advertising on Instagram. This research uses the quantitative methodology and a descriptive content analysis method. 100 samples of dental health service advertising on Instagram from 2017 to 2021 were found through the hashtag #doktergigijogja. The sampling technique used is convenience sampling. The sample was assessed by two coders using a checklist. The research data are presented in descriptive statistics. The maximum number of AIA indications that can be fulfilled is 13 out of 15 indicators. There are 64 advertisements (coder1) and 77 advertisements (coder2) that violate at least one article in The Regulation of the Minister of Health No.1787/2010. There are 31 advertisements (coder1) and 29 advertisements (coder 2) that violate the articles in The Indonesian Dental Code of Ethics 2020. An educational approach by paying attention to the effectiveness of marketing communications while also honoring the dental profession's ethics is a strategy that can be used before posting dental health service advertisements on Instagram. Abstrak: Instagram adalah salah satu jenis media sosial berbasis gambar dan video yang dapat dimanfaatkan oleh dokter gigi sebagai media pemasaran digital untuk mengenalkan merek di benak calon pasien. Dokter gigi harus memperhatikan beragam aspek sebelum menggunggah konten di media sosial, yaitu tercapainya komunikasi pemasaran secara visual juga dengan memperhatikan isu legal dan etik. Tujuan dari penelitian ini adalah untuk menganalisis isi iklan pelayanan kesehatan gigi di Instagram menggunakan model komunikasi pemasaran AISAS, etika iklan dan etika profesi dokter gigi. Penelitian ini menggunakan metode analisis isi deskriptif dengan pendekatan kuantitatif. 100 sampel iklan pelayanan kesehatan gigi di Instagram dari tahun 2017-2021 ditermukan melalui hashtag #doktergigijoga. Teknik sampling yang digunakan adalah convenience sampling. Sampel dinilai oleh dua coder menggunakan daftar periksa. Data hasil penelitian disajikan secara statistik deskriptif. Jumlah indikator AIA terbanyak yang dapat dipenuhi adalah 13 dari 15 indikator. Jumlah iklan melanggar minimal satu pasal pada PMK No.1787/2010 adalah 64 iklan (coder1) dan 77 iklan (coder2). Jumlah iklan melanggar pasal pada KODEKGI 2020 adalah 31 iklan (coder1) dan 29 iklan (coder2). Strategi yang dapat dilakukan dalam menggunggah iklan pelayanan kesehatan gigi di Instagram adalah menggunakan pendekatan edukasi dengan memperhatikan efektivitas komunikasi pemasaran dan tetap menghormati etika profesi kedokteran gigi.